2014
DOI: 10.1002/wnan.1279
|View full text |Cite
|
Sign up to set email alerts
|

Particle‐induced pulmonary acute phase response may be the causal link between particle inhalation and cardiovascular disease

Abstract: Inhalation of ambient and workplace particulate air pollution is associated with increased risk of cardiovascular disease. One proposed mechanism for this association is that pulmonary inflammation induces a hepatic acute phase response, which increases risk of cardiovascular disease. Induction of the acute phase response is intimately linked to risk of cardiovascular disease as shown in both epidemiological and animal studies. Indeed, blood levels of acute phase proteins, such as C-reactive protein and serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
134
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 98 publications
(144 citation statements)
references
References 99 publications
(252 reference statements)
9
134
0
1
Order By: Relevance
“…Unmodified HNTs have shown to induce very low cytotoxicity in the following human cell types: carcinoma cells, peripheral blood lymphocytes, primary umbilical vein endothelial cells, intestinal cells, and epithelial cells (Ahmed et al, 2015;Vergaro et al, 2010;Nan et al, 2008;Lai et al, 2013). However, as HNTs have similar dimensions as short carbon nanotubes (CNTs), they may potentially cause pulmonary inflammation and acute phase response following pulmonary exposure as previously reported for CNTs (Saber et al, 2013(Saber et al, , 2014Poulsen et al, 2015Poulsen et al, , 2017Jaurand, 2017).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Unmodified HNTs have shown to induce very low cytotoxicity in the following human cell types: carcinoma cells, peripheral blood lymphocytes, primary umbilical vein endothelial cells, intestinal cells, and epithelial cells (Ahmed et al, 2015;Vergaro et al, 2010;Nan et al, 2008;Lai et al, 2013). However, as HNTs have similar dimensions as short carbon nanotubes (CNTs), they may potentially cause pulmonary inflammation and acute phase response following pulmonary exposure as previously reported for CNTs (Saber et al, 2013(Saber et al, , 2014Poulsen et al, 2015Poulsen et al, , 2017Jaurand, 2017).…”
Section: Introductionmentioning
confidence: 81%
“…Gebel et al (2014) proposed that biodurable HARN that do not meet the fiber paradigm may be classified as granular biodurable particles (GBPs). GBPs are classified as low toxicity particles, which may however cause inflammation and acute phase response (Moreno-Horn and Gebel, 2014;Saber et al, 2014), which in turn are risk factors for cardiovascular disease (Saber et al, 2014). Stanton et al (1981) showed that pleural dose to 40 mg of two different types of HNTs in hardened gelatin implanted on to the pleural surface resulted in formation of pleural sarcomas in 9 of 53 rats (17%) 2 years post-exposure as compared to 3 of 488 sham-treated controls (0.6%).…”
Section: Introductionmentioning
confidence: 99%
“…8,41,42 In contrast to CRP, SAA is more often discussed as causal factor for cardiovascular disease. 15,16,43 Furthermore, SAA exhibits pro-inflammatory characteristics such as the attraction of phagocytes, the induction of proinflammatory cytokines and the delay of neutrophil apoptosis, 11,12 which may contribute to the pathogenesis of atherosclerosis. SAA has been reported to act pro-atherogenic also by driving an increase in vascular biglycan content, predisposing the vessel wall to increased retention of atherogenic lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation was determined as the influx of inflammatory cells in the lung lining fluid [by the cellular composition in the bronchoalveolar lavage (BAL) fluid (BALF)], and BALF protein concentration was assessed as a general marker of lung tissue damage. Saa3 mRNA levels in lung and Saa1 levels in liver were used as biomarkers for acute phase response (24–26). Genotoxicity was assessed as DNA strand breaks determined by comet assay in BAL cells, lung and liver.…”
Section: Introductionmentioning
confidence: 99%